Double Chromosomal Anomalies in Turner Syndrome: Rare Co-existence of Robertsonian Translocation with Monosomy X and Isochromosome XQ - Sinkar, Prachi; Iyer, Sandhya (Asian Journal of Biological and Life Sciences, 2020)
Background and Aim:The co-existence of a Robertsonian translocation with Turner Syndrome (TS) or variant of Turner Syndrome (isochromosome Xq) is an uncommon phenomenon. In this report we present two cases with double chromosomal anomalies.Case Report:In the first case, we present findings from a 19 years old female, detected to harbor classic TS combined with t(13;14) Robertsonian translocation. The second case involves a 13 years old female, with isochromosome Xq10 (a known variant of Turner Syndrome) combined with t(13;14) Robertsonian translocation.Conclusion:Literature around double chromosome anomalies were found to be few and our case report is one of the first few to identify structural abnormality of X chromosome (isochromosome X) along with a t(13;14) Robertsonian translocation.
Keywords: Isochromosome XQ; Karyotype; Primary amenorrhea; Robertsonian translocation; Turner syndrome